Orthogonal Click Conjugation to the Liposomal Surface Reveals the Stability of the Lipid Anchorage as Crucial for Targeting. Issue 33 (12th July 2016) - Fritz, Thomas; Voigt, Matthias; Worm, Matthias; Negwer, Inka; Müller, Sophie S.; Kettenbach, Kathrin; Ross, Tobias L.; Roesch, Frank; Koynov, Kaloian; Frey, Holger; Helm, Mark
Abstract: Synthetic access to multiple surface decorations are a bottleneck in the development of liposomes for receptor mediated targeting. This opens a complex multiparameter space, exploration of which is severely limited in terms of sample numbers and turnaround times. Here, we unlock this technological barrier by a combination of a milligram‐scale liposome formulation using dual centrifugation and orthogonal click chemistry on the liposomal surface. Application of these techniques to conceptually new amphiphilic compounds, which feature norbornene and alkyne groups at the apex of sterically stabilizing, hyperbranched polyglycerol moieties, revealed a particular influence of the membrane anchor of functional amphiphiles. Folic acid residues clicked to cholesterol‐based amphiphiles were inefficient in folate‐mediated cell targeting, while dialkyl‐anchored amphiphiles remained stable in the liposomal membrane and imparted efficient targeting properties. These findings are of specific importance considering the popularity of cholesterol as a lipophilic anchor. Abstract : Orthogonal on‐surface modifications : Milligram scale liposome formulations by dual centrifugation were combined with orthogonal click chemistry, using conceptually new amphiphilic polyglycerol compounds bearing norbornene and alkyne groups. In vitro interactions imply a crucial influence of the lipid anchor on the targeting properties of liposomes, questioning the popularity of cholesterol as a lipophilic anchor.